State Estimators for Uncertain Linear Systems with Different Disturbance/Noise Using Quadratic Boundedness - Longge Zhang; Xiangjie Liu; Xiaobing Kong (Journal of Applied Mathematics)
This paper designs state estimators for uncertain linear systems with polytopic description, different state disturbance, and measurement noise. Necessary and sufficient stability conditions are derived followed with the upper bounding sequences on the estimation error. All the conditions can be expressed in the form of linear matrix inequalities. A numerical example is given to illustrate the effectiveness of the approach.